Benefits of Prophylactic Short-Course Immune Tolerance Induction in Patients With Infantile Pompe Disease: Demonstration of Long-Term Safety and Efficacy in an Expanded Cohort - Desai, Ankit K.; Baloh, Carolyn H.; Sleasman, John W.; Rosenberg, Amy S.; Kishnani, Priya S. (Frontiers in Immunology, 2020)
Immune tolerance induction (ITI) with a short-course of rituximab, methotrexate, and/or IVIG in the enzyme replacement therapy (ERT)-naïve setting has prolonged survival and improved clinical outcomes in patients with infantile Pompe disease (IPD) lacking endogenous acid-alpha glucosidase (GAA), known as cross-reactive immunologic material (CRIM)-negative. In the context of cancer therapy, rituximab administration results in sustained B-cell depletion in 83% of patients for up to 26-39 weeks with B-cell reconstitution beginning at approximately 26 weeks post-treatment. The impact of rituximab on serum immunoglobulin levels is not well studied, available data suggest that rituximab can cause persistently low immunoglobulin levels and adversely impacting vaccine responses. Data on a cohort of IPD patients who received a 4-week course of rituximab and had ≥6 months of follow-up were retrospectively studied. B-cell quantitation, immunization history, and vaccine titers after B-cell reconstitution were reviewed. Data were collected for 34 IPD patients (25 CRIM-negative and 9 CRIM-positive) with a median age at ERT initiation of 3.5 months (0.1-11.0 months). B-cell reconstitution, as measured by normalization of CD19%, was seen in all patients (n=33) at a median time of 17 weeks range (11-55 weeks) post-rituximab. All maintained normal CD19% with the longest follow-up being 248 weeks post-rituximab. 30/34 (88%) maintained negative/low anti-rhGAA antibody titers, even with complete B-cell reconstitution. Infections during immunosuppression were reported in five CRIM-negative IPD patients, all resolved satisfactorily on antibiotics. There were no serious sequelae or deaths. Of the 31 evaluable patients, 27 were up to date on age-appropriate immunizations. Vaccine titers were available for 12 patients after B-cell reconstitution and adequate humoral response was observed in all except an inadequate response to Pneumococcal vaccine (n=2). These data show the benefits of short-course prophylactic ITI in IPD both in terms of safety and efficacy. Data presented here is from youngest cohort of patients treated with rituximab and expands the evidence of its safety in the pediatric population.